Exploring the Role of Magnetotherapy, Laser Therapy, Electrotherapy, and Cryotherapy in Rheumatoid Arthritis Treatment: A Review - Kiełbratowska , Julia; Lewandowski , Mikołaj; Kwiatkowska, Zofia; Mikulska, Jowita; Sepioło , Weronika; Wąsik, Joanna; Gryboś, Kacper; Kurkiewicz, Wojciech; Woźniak, Oskar (Quality in Sport, 2025)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune connective tissue disorder that leads to disability, impairment and premature mortality. As non-pharmacological approaches that do not interfere with existing treatments, magnetotherapy, laser therapy, electrotherapy and cryotherapy present promising supplemental options. Although they are employed in the treatment of RA patients,their mechanisms of action and advantages are not fully understood and remain an area of ongoing research. Aim of the Study: This review explores the mechanisms of magnetotherapy, laser therapy, electrotherapy andcryotherapy and evaluates their effects on inflammation, oxidative stress, pain, and functional outcomes in RA, providing insights into their potential as a complementary treatment and identifying potential risks. Materials and Methods: A review of research literature was conducted through databases such as PubMed, Google Scholar, ResearchGate, and the Cochrane Library Results: The studied methods effectively reduced pain and disease activity in RA patients. Conclusions: These methods can complement conventional treatments, but further research is needed to standardize protocols and assess risks.